The Effects of Exercise in Hypoxia and Normoxia Conditions on Endothelin-1 and EPO in Endurance Runners - Roohollah Mohammadi Mirzaei (Allameh Tabataba'i University Press, 2020)
Purpose: The purpose of this study was to determine the effects ''living high, training high and low'' (LHTLH) protocol on serum endothelin-1 and erythropoietin protein levels and 5000 m performance Iranian national team endurance runners. Method: Eight male runners (age of 24.4±3.1 years, height of 180.5±4.2 cm, weight of 66.7±3.4 kg, BMI of 20.1±5.0 kg/m2) voluntary participated in this research along with dedicated exercises with the running at middle distance to marathon method in high and low altitudes. 5000 m test accomplished for all study cases and blood samples were taken before and 24 hours after that. The exercises were including continues, interval, aerobic and resistance trainings. Runners were planned to have sixteen training session per week on at long time for 11 weeks live high-train high and low altitude participate in period training. Results: Data were collected and analyzed by analysis of variance with repeated measures (P≤0.05). 5000 m running time significantly decreased related to time effect before and after training. No significant changes were observed in EPO (P≥0.05). But endothelin-1 was significantly increased before to after training protocol (P≤0.05). Conclusions: In this study showed that specific training program decreases 5000 m running time in lower altitude not because of its direct effect on EPO Level changes but hematological and metabolism changes and increase endothelin-1 levels might to be the real cause performance improve of that in hypoxic and normoxia condition.